2018
DOI: 10.1016/j.anihpc.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Partial data inverse problems for Maxwell equations via Carleman estimates

Abstract: Abstract. In this article we consider an inverse boundary value problem for the timeharmonic Maxwell equations. We show that the electromagnetic material parameters are determined by boundary measurements where part of the boundary data is measured on a possibly very small set. This is an extension of earlier scalar results of BukhgeimUhlmann and Kenig-Sjöstrand-Uhlmann to the Maxwell system. The main contribution is to show that the Carleman estimate approach to scalar partial data inverse problems introduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…These are elliptic systems that generalize the scalar Schrödinger equation (−△ + q)u = 0 and are very close to the time-harmonic Maxwell equations when n = 3. In fact, using the results of the present paper, we have finally been able to extend the partial data result of [KSU07] to the Maxwell system [COST15]. The main technical contribution of the present paper is a Carleman estimate for the Hodge Laplacian, with limiting Carleman weights, that has boundary terms involving the relative and absolute boundary values of graded forms.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…These are elliptic systems that generalize the scalar Schrödinger equation (−△ + q)u = 0 and are very close to the time-harmonic Maxwell equations when n = 3. In fact, using the results of the present paper, we have finally been able to extend the partial data result of [KSU07] to the Maxwell system [COST15]. The main technical contribution of the present paper is a Carleman estimate for the Hodge Laplacian, with limiting Carleman weights, that has boundary terms involving the relative and absolute boundary values of graded forms.…”
mentioning
confidence: 64%
“…We expect that the methods developed in this paper open the way for obtaining partial data results via Carleman estimates for various elliptic systems. This has already been achieved for Maxwell equations [COST15].…”
mentioning
confidence: 76%
“…In [43], an inverse boundary value problem for the time-harmonic Maxwell equations was considered. The authors showed that the electromagnetic material parameters were determined by boundary measurements where part of the boundary data is measured on a possibly very small set.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its versatility and robustness, this technique has since become the standard tool for solving partial data elliptic inverse problems. The review article [19] contains an excellent overview of recent work in partial data Calderón-type problems; examples for other elliptic inverse problems can be found in [31], [32], [22], [9], and [8].…”
Section: Introductionmentioning
confidence: 99%